Technological Innovations and their Role in Transformation of Agriculture in India: An Analytical Study - BHARDWAJ, RAJNEESH (International Journal of Psychosocial Rehabilitation, 2024)
The agrarian sector is a momentous contributor to the Indian economy, with a considerable number of people reliant on it for sustenance. The adoption of technological innovations has played a crucial role in revolutionizing agriculture in India. This study examines the function of technological innovations in the agrarian sector of India with a spotlight on the impact of advancements such as precision farming, genetically modified crops, mobile technology, and blockchain on productivity, profitability, and sustainability. The research has concluded that technological innovations have noticeably enhanced agrarian practices in India by optimizing resource utilization, amplifying yields, and curbing costs. The Green Revolution played a pivotal role in elevating food production, while precision farming has facilitated farmers in diminishing input expenses and improving crop management practices. Genetically modified crops have resulted in increased yields and reduced crop losses due to pests and diseases. Mobile technology has allowed farmers to access real-time information, leading to informed decision-making and increased profits. In general, technological innovations have transformed agriculture in India and will persist in playing a pivotal role in its expansion and advancement.